2007
DOI: 10.1002/hlca.200790014
|View full text |Cite
|
Sign up to set email alerts
|

New Eremophilane Sesquiterpenes from a Rhizome Extract of Petasites hybridus

Abstract: A total of 21 natural products, 1 -21, were isolated from a supercritical CO 2 extract of the rhizomes of Petasites hybridus. Thereby, seven new eremophilane (= (1S,4aR,7R,8aR)-decahydro-1,8a-dimethyl-7-(1-methylethyl)naphthalene) sesquiterpenes, compounds 4, 5, 9, 11, 12, 15, and 17, were identified. The new constituent 9-hydroxyisobakkenolide (15) is the first representative of a group of compounds closely related to the well-known, but rare, bakkenolides. Tsoongianolide B (18) and its degradation product li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…18,19 Most of the older publications show CD spectra of Petasites compounds beginning far above 200 nm and/or only indicate the sign and De values of the most important extrema. Therefore, we aimed to present complete CD spectra of several quite similar eremophilane type sesquiterpenes and to achieve certain knowledge how the minimal structural differences of these compounds could contribute to the spectroscopic influence of the carbonyl group.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…18,19 Most of the older publications show CD spectra of Petasites compounds beginning far above 200 nm and/or only indicate the sign and De values of the most important extrema. Therefore, we aimed to present complete CD spectra of several quite similar eremophilane type sesquiterpenes and to achieve certain knowledge how the minimal structural differences of these compounds could contribute to the spectroscopic influence of the carbonyl group.…”
mentioning
confidence: 98%
“…C NMR experiments have been described recently. 19 The UV-characterization of all compounds in methanol is compiled in Table 1. A Shimadzu UV-visible recording spectrophotometer UV-160A and a quartz cuvette with 1 cm path-length were used for UVphotometry.…”
mentioning
confidence: 99%
“…3). The NOE enhancements for H-14/H-3 β , H-14/H-6, H-14/H-10, H-15/H-3 β and H-4/H-6 indicated that these compounds contain a cis-decalin ring system with a steroidal-like conformation 7,10) and that each acyl group was in the β-orientation. Furthermore, the direction of methoxy group (C-16) was determined to be β-orientation according to the above mentioned rules reported by Naya et al [8][9][10] Based on these results, the relative stereochemistries of culcitiolides F and G were determined as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The negative Cotton effects, observed at 245 nm, substantiated the absolute configuration of C-8 to be R. 8,10) Culcitiolides F and G (2, 3) were purified as an inseparable mixture of two structural isomers. The molecular formulas of these isomers were established by HR-FAB-MS as C 21 4,5,7,11) with the ratio of 1 to 1. These signals suggest that compound 2 is an eremophilane-type sesquiterpenoid with a senecioyl group and that 3 is a structural isomer of 2 at the tigloyl group (C-2′ and C-3′).…”
Section: Resultsmentioning
confidence: 99%
“…Exemplos de substâncias naturais com atividade biológica que possuem este arranjo de anéis são os membros da classe de sesquiterpenóides bacanos [1][2][3][4] e tapsanos (Figura 1), 5,6 bem como alguns produtos naturais relacionados com eremofilanos. 7,8 Diversas estratégias têm sido utilizadas para a construção do sistema cis-hidrindânico [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Introductionunclassified